ANALISIS KESALAHAN BERBAHASA TATARAN SINTAKSIS PADA TEKS BERITA SISWA KELAS VIII SMPN 2 PANGENAN CIREBON TAHUN PELAJARAN 2021/2022 - Riri Mukhariroh; Emah Khuzaemah; Tati Sri Uswati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This research is a qualitative descriptive study with the subject of this research in the form of a document of the results of the VIII grade students of SMPN 2 Pangenan Cirebon. Data collection techniques used by researchers in this study are in the form of documentation techniques and note-taking techniques. Meanwhile, the validity checking technique used triangulation technique. The data analysis used in this study used the agih method and continued using the basic technique for direct elements or the BUL technique. After using the basic technique, it was continued using advanced techniques, namely by using the lesap technique, the replacement technique, the reverse technique, and the extension technique to facilitate data analysis. The results of this study are in the form of a description of the analysis of language errors at the syntactic level in the student news text. The results are 39 forms of phrase errors and 11 forms of sentence errors. With the results of the analysis of language errors at the syntactic level, educators should be able to obtain an overview of appropriate learning models, methods, and media to support the improvement of students' writing skills, especially in the field of syntax.. Keywords: Language Error, Syntax, News Text